Application of numerical water force to a small sport boat running on a lake - Tran, H.T.; Bikowski, S.; Wolf, C. D.; Maiber, P. (Vietnam Journal of Mechanics, 2003)
In this paper the motion of a small sport boat running on a lake is simulated using alaska tools. External forces and torques from water during movement have been taken into account. Using results from measurements the simulation has been validated.